The Influence of the Concept of Active Longevity on the Quality of life of the Older adults (the case of Almaty): Qualitative Research (The Journal of Psychology and Sociology, 2026)
Population ageing is a global demographic trend that significantly influences the socio-economic development of society. The purpose of this study is to identify the impact of the “Active Longevity Concept” on the quality of life of older adults. Understanding the factors that influence active ageing and the quality of life of older adults is essential for developing effective strategies and projects in the field of healthcare and social welfare.The study involved older adults receiving services from the “Active Longevity” Center in Almaty. The empirical part of the research was conducted using the in-depth interview method. A total of 10 respondents aged 58–75 participated in the interviews. The obtained data were coded and processed using the specialized MAXQDA software for qualitative data analysis.The results of the study identified the main factors affecting the quality of life of older adults: economic conditions, physical and mental health status, and the level of social connections. Data analysis showed that the main sources of income for older adults are pensions and financial support from their children. Among the most common problems after retirement are health deterioration, financial constraints, feelings of loneliness, and weakening social ties. The results of the study also indicate the need to establish similar centers adapted to rural areas. The practical significance of the study lies in the possibility of using the obtained results in the development of social programs and projects aimed at creating conditions for active and high-quality ageing. The findings may contribute to improving the financial, educational, organizational, and informational instruments of state policy on active longevity and to developing recommendations for increasing the activity and quality of life of older adults.Keywords: older adults, population ageing, quality of life, active longevity, social policy.